THE EFFECT OF PUBLIC ACCOUNTABILITY, BUDGET PARTICIPATION AND INTERNAL CONTROL ON THE PERFORMANCE AT THE DINAS KESEHATAN KAMPAR DISTRICT - Sinta Alviani; Rahmawati Rahmawati; Helmiati Helmiati (STIE Bangkinang Publishing, 2020)
Research to determine the effect of public accountability, budget participation and intenal control on the public service performance with simulthan and partial at the Dinas Kesehatan Kampar District. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this study were all employees at the Dinas Kesehatan Kampar District, while the sampling was carried out using purposive sampling obtained as many 60 employees at the Dinas Kesehatan Kampar District. Based on the simulthan test results, the variable of public accountability, budget participation and intenal control have a significant effect with together on the performance at the Dinas Kesehatan Kampar District, while based on the partial test results, the variable of public accountability, budget participation and intenal control have a significant effect with individual on the performance at the Dinas Kesehatan Kampar District the closeness of the relationship that occurs between the atractiveness of public accountability, budget participation and intenal control on the performance is very strong with a correlation coefficient R of 88,3%, while contribution of public accountability, budget participation and intenal control on the performance is equual to 77,9% while the remaining is 22,1% againt influenced by other variables not examined in this study.